Revolution and philosophy : a study of the significance of the French Revolution for the social and political philosophies of Hegel and Marx - Prior, Buxton John Vere (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1971.